Factors associated with home advantage in English and Scottish soccer matches - Nevill, A. M.; Newell, S. M.; Gale, S. (Journal of Sports Sciences, 1996)
Using the results from the end-of-season (1992-93) league tables, overall home advantage was confirmed in the eight major divisions of the English and Scottish football leagues. The degree of home advantage was found to vary significantly across the divisions. Furthermore, these divisional differences in home advantage were found to be significantly associated with the mean attendance of each division. In an attempt to understand these findings, every occurrence of two influential events (either a sending-off or penalty scored) reported in a national Sunday newspaper was recorded. The overall frequency of both sendings-off and penalties scored favoured the home side, but again this was not constant across the divisions. In divisions with large crowds, the percentage of home sendings-off was relatively small (30%), compared with no difference (50%) in divisions with smaller crowds. Similarly, the percentage of penalties scored by home sides in divisions with the largest crowds was large ( > 70%), in contrast to little or no advantage in divisions with smaller crowds. Two possible explanations for these findings were proposed. Either larger crowds were able to provoke the away player into more reckless behaviour (real fouls), or influence the referee into believing that the away player had committed more fouls (perceived fouls).